Effect of Tai Chi Chuan in Breast Cancer Patients: A Systematic Review and Meta-Analysis - Luo, Xiao-Chao; Liu, Jie; Fu, Jia; Yin, Hai-Yan; Shen, Li; Liu, Mai-Lan; Lan, Lei; Ying, Jian; Qiao, Xiu-Lan; Tang, Chun-Zhi; Tang, Yong (Frontiers in Oncology, 2020)
Background Tai Chi Chuan(TCC), as a mind-body exercise, may have a positive effect on physical function and psychological well-being in breast cancer patients. The latest systematic review and meta-analysis of TCC for breast cancer was made four years ago and some new clinical trials about it were published. We remade a systematic review and meta-analysis to assess the effect of TCC in breast cancer patients. Methods In this systematic review and meta-analysis, we searched MEDLINE (via PubMed), EMBASE (via embase.com), CENTRAL, CNKI, VIP, Wanfang, Chaoxing, CiNii, J-SSTAGE, DBpia and ThaiJO with no language restrictions from inception to December 31, 2018 (updated on February 16, 2020), for randomized clinical trials comparing TCC with non-exercised therapy in breast cancer patients. The primary outcome was quality of life in patients with breast cancer and data pooled by a random-effects model. Subgroup analyses were done to estimate the effect of different duration of TCC for breast cancer patients. This study was registered with PROSPERO, number CRD 4201810326. Results Fourteen articles involving a total of 885 breast cancer participants were included in this review. Compared with non-exercised therapy, TCC had a significant effect on quality of life in breast cancer patients (SMD=0.37, 95% CI 0.15 to 0.59, p=0.001), and subgroup analysis found that TCC showed beneficial effect in 12 weeks and 25 weeks (12 weeks: SMD=0.40, 95% CI 0.19 to 0.62, p=0.0003; 25 weeks: SMD=0.38, 95% CI 0.15 to 0.62, p=0.002). Meta-analyses of secondary outcomes showed that 3 weeks TCC increased shoulder function (SMD=1.08, 95% CI 0.28 to 1.87, p=0.008), 12 weeks TCC improved pain (SMD=0.30, 95% CI 0.08 to 0.51, p=0.007), shoulder function (SMD=1.34, 95% CI 0.43 to 2.25, p=0.004), strength of arm (SMD=0.44, 95% CI 0.20 to 0.68, p=0.0004), and anxiety (MD=-4.90, 95% CI -7.83 to -1.98, p=0.001) in breast cancer patients compared with the control group. Conclusions TCC appears to be effective on some physical and psychological symptoms and improves quality of life in patients with breast cancer. Additional randomized controlled trials with rigorous methodology and low risk of bias are needed to provide more reliable evidence.